2018
DOI: 10.2147/dddt.s157115
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium: does it reduce ischemia/reperfusion injury in an adnexal torsion rat model?

Abstract: AimThe aim of the present study was to assess the protective effects of magnesium sulfate (MgSO4) on ischemia/reperfusion (I/R) induced ovarian damage in a rat ovarian torsion model.MethodsForty-two female Sprague Dawley rats were included in the study. They were divided into six groups as Group 1, sham; Group 2, bilateral ovarian torsion; Group 3, bilateral ovarian torsion–detorsion; Group 4, MgSO4–sham; Group 5, MgSO4–bilateral ovarian torsion; Group 6, bilateral ovarian torsion–MgSO4–detorsion. Both torsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Lipid peroxidation causes loss of cell membrane integrity, increased permeability to ions, and cell damage. Therefore, inhibiting or reducing the lipid peroxidation process may help prevent tissue damage (26,27). Our study found that MDA levels increased in torsion and torsion-detorsion groups compared to the sham group.…”
Section: Discussionmentioning
confidence: 60%
“…Lipid peroxidation causes loss of cell membrane integrity, increased permeability to ions, and cell damage. Therefore, inhibiting or reducing the lipid peroxidation process may help prevent tissue damage (26,27). Our study found that MDA levels increased in torsion and torsion-detorsion groups compared to the sham group.…”
Section: Discussionmentioning
confidence: 60%
“…Oxidative stress caused by pathological ROS overproduction is closely related to the development of ischemia–reperfusion injury in ovaries. Since management of ovarian torsion by detorsion causes a form of ischemia–reperfusion injury, measures taken to avoid this damage also became important in the area of gynecology 25 …”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] For this reason, performing detorsion procedures is critical to maintain the viability of ischemic ovarian tissue. [ 7 ] However, these procedures can also induce adverse changes in the tissue. Reoxygenation of hypoxic tissue leads to the formation of excessive reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%